Classroom Management and Students’ English Skills - Dzahabiyyah, Launia; Zharfa, Ratri Izzati; Mulyono, Safira Indah Putri; Pramesti, Magdalena Ayu Sri (STIBA IEC JAKARTA, 2024)
The aim of this study was to examine how teachers implement classroom management in private tutoring classes for elementary school students and determine if these classes contribute to students' English skills. The research was conducted at a private English course in Semarang on April 24th 2024. Research method used is a qualitative method with case studies. Research techniques used are observation and structured interviews. The findings of the study have been presented in three categories of classroom management, that are: Teaching Standards, Rules, and Procedures, Classroom Climate, and Timing and Scheduling. Based on the results, teachers’ Classroom Management contributes to the students’ English skills.